Potential Pharmaceutical and Biomedical Applications of Diatoms Microalgae - An Overview - Kuppusamy, Palaniselvam; Soundharrajan, Ilavenil; Natanamurugaraj, Govindan; Srigopalram, Srisesharam; M. M., Yusoff; Gaanty Pragas, Maniam; Choi, Ki Choon (NISCAIR-CSIR, India, 2017)
Naturally occurring two girdle band valves of diatoms are made up of siliceous material as covering the cell wall of the organism. The unicellular microalgae are coming under bacillariophyceae groups and identified more than 10,000 species. It found in various natural sources such as sea water, river, ponds and wastewater. Diatom is very small in size approximately 20-200 nm. The microalgae diatoms are used in pharmaceutical and biomedical industries due to the smaller in size and structure. Also, the nanoscale structures of diatom frustules are highly observed and using as a drug delivery material for therapeutic approaches. On other hand, diatom is one of the main sources of the food chain in the marine system. It is the photosynthetic organism which synthesis the required foods themselves by photosynthesis. Diatoms utilize the atmospheric CO2 and releases oxygen through the biochemical process and maintain the atmospheric CO2 level when the biological process occurred. In addition, the diatom microalgae contain the high amount of unsaturated fatty acids (50-60%), lipids, polysaccharides and other biomolecules which are used in the chronic and acute diseases treatments. In this review, we are mainly focused on the diatoms for therapeutic applications in different pharmaceutical and biomedical arena.